2017
DOI: 10.1002/em.22137
|View full text |Cite
|
Sign up to set email alerts
|

Comparing BMD‐derived genotoxic potency estimations across variants of the transgenic rodent gene mutation assay

Abstract: There is growing interest in quantitative analysis of in vivo genetic toxicity dose‐response data, and use of point‐of‐departure (PoD) metrics such as the benchmark dose (BMD) for human health risk assessment (HHRA). Currently, multiple transgenic rodent (TGR) assay variants, employing different rodent strains and reporter transgenes, are used for the assessment of chemically‐induced genotoxic effects in vivo. However, regulatory issues arise when different PoD values (e.g., lower BMD confidence intervals or B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…To ensure consistency of the analyses across the tested substances, the dose–response data were analysed using a five parameter exponential model. BMD-covariate analyses often assume that some model parameters (e.g., c and d for maximum response and log-steepness after axis scaling) are constant across covariate sub-groups (Wills et al 2017 ); this is consistent with the work of (Slob and Setzer 2014 ). The AIC (Akaike Information Criterion) was used for model selection, and post-hoc analyses statistically evaluated the effect of sampling time on any retained parameter.…”
Section: Methodsmentioning
confidence: 84%
“…To ensure consistency of the analyses across the tested substances, the dose–response data were analysed using a five parameter exponential model. BMD-covariate analyses often assume that some model parameters (e.g., c and d for maximum response and log-steepness after axis scaling) are constant across covariate sub-groups (Wills et al 2017 ); this is consistent with the work of (Slob and Setzer 2014 ). The AIC (Akaike Information Criterion) was used for model selection, and post-hoc analyses statistically evaluated the effect of sampling time on any retained parameter.…”
Section: Methodsmentioning
confidence: 84%
“…This is critically important since it provides a means for determining the precision of the BMD; moreover, it's utility for risk assessment and regulatory decision-making. More specifically, the ratio of the BMDU to the BMDL provides information about the uncertainty of the BMD, which in turn reflects the quality of the underlying dose-response data(Wills et al 2017). Indeed, it has been suggested that the magnitude of uncertainty of the BMD estimate, as indicated by the BMDL to BMDU ratio, should be used as a tool for evaluating the statistical quality of the underlying data(Benford et al 2010), and the utility of a BMDL as a reference PoD for regulatory decision-making(Barlow et al 2006;Benford et al 2010).…”
mentioning
confidence: 99%
“…aneugens 37 . This is less accepted for a DNA reactive compounds 38 . However, the generation of high content quantitative dose response data, such as that in this assay, could enable safe dose margins or thresholds to be established for compounds using benchmark dose considerations 38 .…”
Section: Discussionmentioning
confidence: 99%